Women and Mental Health: A Literature Review on Gender-Specific Challenges and Support Systems - Rismala Dewi; Misbah; Endah Sulistiawati; Nabilla Novella Riyanti (WISE Pendidikan Indonesia, 2025)
Women’s mental health has become a major global issue, as women experience higher rates of psychological disorders than men due to the interaction of biological, social, and cultural factors. This study aims to synthesize research on gender-specific challenges and support systems influencing women’s psychological well-being. Using a literature review approach, the study systematically analyzed empirical and conceptual studies published between 2018 and 2025 from Scopus, Web of Science, Taylor & Francis, SpringerLink, SAGE Journals, and nationally accredited SINTA 1–2 sources. From 132 identified articles, nine met the inclusion criteria after screening and full-text evaluation. Data were analyzed thematically using Aveyard’s and Randolph’s frameworks to identify major patterns and conceptual links. The results reveal two dominant themes: gender-specific challenges such as role overload, social pressure, and gender-based violence and support systems involving family, community, policy, and digital networks that strengthen women’s mental resilience. The study concludes that effective approaches to improving women’s mental health must be gender-sensitive, interdisciplinary, and contextually grounded. Its implications call for inclusive mental health policies, stronger community support, and the development of ethical and accessible digital services for women worldwide.